Advances in Computer Science and Ubiquitous Computing CSA-CUTE2016 - Park, James J. (Jong Hyuk).; Pan, Yi.; Yi, Gangman; Loia, Vincenzo; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents the combined proceedings of the 8th International Conference on Computer Science and its Applications (CSA-16) and the 11st International Conference on Ubiquitous Information Technologies and Applications (CUTE 2016), both held in Bangkok, Thailand, December 19 - 21, 2016. The aim of these two meetings was to promote discussion and interaction among academics, researchers and professionals in the field of ubiquitous computing technologies. These proceedings reflect the state-of-the-art in the development of computational methods, involving theory, algorithm, numerical simulation, error and uncertainty analysis and novel application of new processing techniques in engineering, science, and other disciplines related to ubiquitous computing.
CUTE2016 -- 1 Ubiquitous Communication and Networking -- 2 Ubiquitous Software Technology -- 3 Ubiquitous Systems and Applications -- 4 Ubiquitous Security, Privacy and Trust -- CSA2016 -- 1 Mobile and ubiquitous computing -- 2 Dependable, reliable and autonomic computing -- 3 Security and trust management -- 4 Multimedia systems and services -- 5 Networking and communications -- 6 Database and data mining -- 7 Game and software engineering -- 8 Grid and scalable computing -- 9 Embedded system and software -- 10 Artificial intelligence -- 11 Distributed and parallel algorithms -- 12 Web and internet computing -- 13 IT policy and business management. .
Keywords: Telecommunication; Computational intelligence; Computer networks .; Communications Engineering, Networks; Computational Intelligence; Computer Communication Networks